ANALISIS LITERASI DIGITAL MAHASISWA CALON GURU BIOLOGI MELALUI PROYEK VIDEO AMATIR BERBASIS POTENSI LOKAL PADA MATA KULIAH EKOLOGI TUMBUHAN - Kahar, Adi Pasah (Pedagogi Hayati, 2018)
The purpose of this study to know the degree of digital literacy of the students teacher towards video project based on local potency in West Borneo. This study uses descriptive qualitative methods. The subjects of the study was taken by using systematic sampling technic. The technic of collecting data uses the indirect communication, observation, and direct communication. Collecting data uses observation sheet, and dialogue sheet. The technic of data analysis uses descriptive statistical analysis. The result of the study shows that the degree of the digital literacy of the students is high. It means that the students can use computer (71%) and the ability to use internet (63%). The degree of the digital literacy of the students is moderate. It means that the percentage of the students who can use internet to find biology information only (61%), the percentage of reading biology books via internet only (58%), and to spread and to criticize biological information (58%). The degree of digital literacy is regarded low. This can be seen from having social net to inform about biology (8%) and to distinguish the sources eithen valid or invalid (8%), the ability to find information about biology (3%), and the ability to produce media to spread information of biology (5%). Based on the result get, can be concluded that the degree of digital literacy of students are medium level.